Development of a comparative genomic hybridization microarray and demonstration of its utility with 25 well-characterized 1p36 deletions - Yu, Wei; Ballif, Blake C.; Kashork, Catherine D.; Heilstedt, Heidi A.; Howard, Leslie A.; Cai, Wei-Wen; White, Lisa D.; Liu, Wenbin; Beaudet, Arthur L.; Bejjani, Bassem A.; Shaw, Chad A.; Shaffer, Lisa G. (Human molecular genetics, 2003)
Chromosomal abnormalities, such as deletions and duplications, are characterized by specific and often complex phenotypes resulting from an imbalance in normal gene dosage. However, routine chromosome banding is not sensitive enough to detect subtle chromosome aberrations (<5–10 Mb). Array-based comparative genomic hybridization (array CGH) is a powerful new technology capable of identifying chromosomal imbalance at a high resolution by co-hybridizing differentially labeled test and control DNAs to a microarray of genomic clones. We used a previously assembled contig of large-insert clones that span 10.5 Mb of the most distal region of 1p36 to design a microarray. The array includes 97 clones from 1p36, 41 clones from the subtelomeric regions of all human chromosomes, and three clones from each of the X and Y chromosomes. We used this microarray to study 25 subjects with well-characterized deletions of 1p36. All array CGH results agree with the deletion sizes and locations of the breakpoints in these subjects as determined previously by FISH and microsatellite analyses. Terminal deletions, interstitial deletions, derivative chromosomes and complex rearrangements were also identified. We anticipate that array CGH will change the diagnostic approach to many congenital and acquired genetic diseases such as mental retardation, birth defects and cancer.